Strategi Group Investigation untuk Pembelajaran Sejarah di Era Society 5.0: Tantangan dan Solusi - Muhammad Thoriqun Najah Zain; Aditya Nugroho Widiadi (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan)
Group Investigation is a learning model that is considered appropriate and effective in learning history in the era of society 5.0, but in an era that continues to develop and is fast-paced, the challenges faced in implementing group investigation strategies also vary. In line with these problems, the author intends to provide solutions related to the challenges faced in implementing the Group Investigation learning model in learning history in the era of society 5.0. This research uses a qualitative approach to the literature study method, through the technique of collecting sources relevant to the discussion within the last 10 years. Secondary data was obtained through interviews with teachers in a private institution randomly to ask about the problems experienced by teachers and students at this time. The results of this study show four challenges in applying the group investigation model to learning in the era of society 5.0 including, the character of students today, the background of teachers in accepting technology, the misuse of technology by students, and the uneven distribution of the use of learning. This problem is based on several aspects including individual students, teachers, and schools. The role of teachers in facing this challenge is crucial, where teachers are the main actors in the classroom. So it requires teachers to create a conducive and systematic learning environment. In line with this statement, the solution provided not only refers to the needs of students in teaching and learning activities but also involves teacher creativity in implementing learning. So that the challenges in applying the group investigation learning model can be resolved easily and accurately.